MARITIME LEGISLATIONS: ARE DECISIONS OF THE TRIBUNALS ENFORCEABLE? - OJHA , K.B (International Journal of Psychosocial Rehabilitation, 2020)
There is very famous maxim called ubiius, ibiremedium, which means where there is a right, there is a remedy. Whenever any right is infringed, or there is a dispute between the parties, the concerned parties may prefer a forum to solve the disputes or to get the required remedies for the damages it has suffered. Similarly, the 1982 Convention contains detailed and complex provisions stating the different forums available for the resolution of the sea disputes.